GUARANTEEING THE TROUBLE-FREE OPERATION OF CAPACITOR BANKS IN POWER-SUPPLY SYSTEMS OF INDUSTRIAL ENTERPRISES - D.A. Gapon (National Technical University "Kharkiv Polytechnic Institute", 2016)
Purpose. The problem of resonance phenomena in power systems of industrial enterprises using capacitor banks for reactive power compensation was detected. Circuit of the capacitor banks tier to downshift main substation tires is present. But there is no common algorithm to calculate and avoid such trouble. The main goal of this article is to introduce some basics for power supply systems with possible resonant circuits engineering. Methodology. At the first step the data on the change of the current in the chemical company network when changing capacitor banks value are received. For these purposes the oscilloscope function of digital protection relay was used. Current data samples were analyzed by spectrum detection software. Most significant levels of the 3rd and 5th harmonics were achieved. Comparison of harmonic distortion levels with and without capacitor bank is given. Results. Achieved data allow making conclusion about overloading reasons of capacitor banks while higher harmonics currents presence. A voltage and current harmonious composition measuring in the absence of power quality analyzers using digital protection relay terminals or emergencies registers are proposed. The necessity of power quality monitoring near capacitor banks connections to avoid resonance phenomena (current and voltage resonance) in industrial power supply systems is proven. The control algorithm of capacitor banks to provide electromagnetic compatibility, while various modes of nonlinear load operation is given. Originality. Using of digital protection relay oscilloscoping for current resonant detection can allow to significally reduce time and cost of solution. Replacement parallel circuit comprising a branch and one active-inductive load to another branch network in the presence of higher harmonics source are proposed. Practical value. A sequence for measuring the levels of harmonic components at the connections of capacitor banks in the absence of specialized instruments is proposed. The algorithm to avoid possible resonance currents in the presence of condensing units is proposed.